Turning the Right Corner : Ensuring Development through a Low-Carbon Transport Sector - Kopp, Andreas; Block, Rachel I.; Limi, Atsushi (Washington, DC: World Bank, 2013)
This report 'Turning the right corner - ensuring development through a low carbon transport sector' emphasizes that developing countries need to transition to a low carbon transport sector now to avoid locking themselves into an unsustainable and costly future. Furthermore, it argues that this transition can be affordable if countries combine policies to reduce greenhouse gas emissions with broader sector reforms aimed at reducing local air pollution, road safety risks, and congestion. This report looks at relationships between mobility, low carbon transport and development, drawing attention to the inertia in transport infrastructure. It complements the analysis by reviewing how climate change is likely to affect operations and infrastructure, cost-effective measures for minimizing negative effects, and policies and decision frameworks. It further highlights current and projected research findings and examples from developing countries. And it concludes that new technology is not enough, and that urgent action is needed before economies become locked into high-carbon growth. It discusses how to reconcile development with the need to curb emissions, looking at three sets of instruments and their limitations: new technologies and alternative fuels, supply-side measures, and demand-side policies. This report also looks at both available funding, such as carbon financing and international assistance, and at ways to generate new resources, considering that accounting for negative externalities dramatically alters the economics of transport investment.